2013
DOI: 10.1149/05011.0453ecst
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Rare Earth Metals from Nd-based Scrap by Electrolysis from Molten Salts

Abstract: The possibilities of recovery of rare earth metals and alloys from Nd-based scrap by electrolysis from high temperature molten salts were investigated. The realization of such a process will eliminate the oxide or halide conversion steps, leading to a more effective and environmental process, as many hydrometallurgical steps are avoided. The NdFeB compound (which could be scrap from the magnet production or demagnetized spent magnet) is placed in the anode compartment from where the rare earth elements present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…If one now considers molten salts, the rare earth element neodymium (Nd) can electrochemically be recovered from NdFeB magnets using molten salt electrolysis [102]. During the process, the solid NdFeB material is directly placed in an anodic compartment with molten fluorinating agents (e.g., AlF 3 , ZnF 2 , FeF 3 and Na 3 AlF 6 ), which coverts Nd from a the magnetic alloy into NdF 3 salt melt [103,104]. The Nd 3+ ions from the molten salt can then be electrodeposited at the cathode.…”
Section: Non-aqueous Electrolytes Based Electrochemical Methodsmentioning
confidence: 99%
“…If one now considers molten salts, the rare earth element neodymium (Nd) can electrochemically be recovered from NdFeB magnets using molten salt electrolysis [102]. During the process, the solid NdFeB material is directly placed in an anodic compartment with molten fluorinating agents (e.g., AlF 3 , ZnF 2 , FeF 3 and Na 3 AlF 6 ), which coverts Nd from a the magnetic alloy into NdF 3 salt melt [103,104]. The Nd 3+ ions from the molten salt can then be electrodeposited at the cathode.…”
Section: Non-aqueous Electrolytes Based Electrochemical Methodsmentioning
confidence: 99%
“…16. Combinations of different salts (LiCl-KCl and NaCl-KCl), compositions, and temperatures (from 873 to 1123 K) were investigated by Martinez et al [82]. The application was further developed by Yasuda et al [54] to prepare RE-Ni alloy from magnet scrap using molten NaCl-KCl-RECl 3 as electrolyte.…”
Section: Electrolysis Using Molten Salt and Ionic Liquidsmentioning
confidence: 99%
“…From EDX analysis of the cross section of a sample obtained at 1.70 V, it was found that RE in the outer layer was selectively dissolved but RE in the inner layer remained undissolved. Martinez et al [82] found that LiCl-based melt offered a better option electrochemically (larger potential separation from the Nd reduction potential) than NaCl-based electrolyte. However, under-potential deposition (UPD) of lithium (i.e., deposition at activity lower than unity) on neodymium made it difficult to deposit Nd free of Li.…”
Section: Electrolysis Using Molten Salt and Ionic Liquidsmentioning
confidence: 99%
“…An effective process for the recycling of rare earth scrap is a major concern since most developed countries import their required rare earth elements 2) . Hydrometallurgical and pyro-metallurgical process routes have been the subject of investigation by a number of researchers [3][4][5][6][7] . However, the drawbacks of hydrometallurgy processes are the low reaction rates and the serious environmental problems arising from the huge amounts of waste water generated in the process, which, in turn, need further processing.…”
Section: Introductionmentioning
confidence: 99%